Replacing routine film-based linac QC tests with EPID measurements: a method to reduce the time required for machine-specific QC. (23rd January 2018) - Agnew, C E; Jeevanandam, P; Sukumar, P; Grattan, M W D
Abstract: Increasingly complex radiotherapy techniques require additional machine-specific quality control (QC). The extra time required for such tests is in addition to existing, well-established QC required for standard linac deliveries. Additional time for QC can be in direct conflict with current cost saving driven practice and patient scheduling. One approach to create additional time for machine specific QC is to review current processes and the frequencies of well-established QC tests. In this work, the potential to transfer radiation field size, asymmetric jaw alignment, multi-leaf collimator (MLC) transmission and MLC rotation tests from film analysis to analysis of digital EPID images was investigated. In-house software was developed in MATLAB ® and commissioned for each test by comparison to film. Following commissioning, EPID analysis was introduced into routine use and the results and trends for these tests from 10 Varian linacs were analysed over 5 yr. Radiation field size measurements were found to be smaller than film due to the steeper penumbra in EPID profiles. This effect was field size dependent. By correcting for this, EPID and film measurements agreed within 0.0 ± 0.5 mm (mean ± 1SD), with drifts of ≤0.3 mm yr −1 in field size measurements. The EPID profile response also results in overestimation of asymmetric jaw alignment measurements, which when accounted for permitted the junction gap to be maintained within ±2 mm. Junction gap was found to drift at <0.15 mm yr −1 . EPID assessment of MLC transmission and MLC rotation were also achievable and maintained within tolerance with trend analysis verifying current recommendations for annual assessment. Overall, a shift from film to EPID analysis for radiation field size, asymmetric jaw alignment, MLC transmission and MLC rotation tests saved 9.5 h machine time and 6.7 h subsequent analysis time annually per linac. This will be further increased as trend analysis over 5 yr has indicated the potential to reduce the frequency of some tests.